Stress system dysregulation in pediatric generalized anxiety disorder associated with comorbid depression. (16th December 2016) - Funke, R.; Eichler, A.; Distler, J.; Golub, Y.; Kratz, O.; Moll, G.H.
Abstract: Because chronic stress is an important risk factor for anxiety states and depressive disorders, we studied hypothalamus–pituitary–adrenal (HPA) axis and sympathetic system activity via changes in cortisol and alpha amylase activity levels in pediatric generalized anxiety disorder (GAD) patients ( n = 26) with comorbid depression and a healthy comparison group ( n = 26). Morning plasma cortisol and diurnal profiles of salivary cortisol and salivary alpha amylase (sAA) activity were assessed, also reactivity of HPA‐axis, sAA activity, and heart rate following a psychosocial stressor (Trier Social Stress Test for children). GAD patients with comorbid depression showed increased morning plasma and salivary cortisol levels, ameliorating throughout in‐patient treatment, and higher sAA activity in their diurnal profile. Both HPA and sympathetic activity positively correlated with the severity of anxiety and depression. We also demonstrated a blunted HPA and sympathetic response to acute stress in patients. This pattern of neuroendocrine and sympathetic changes seems to be distinct from the one previously reported in pediatric patients with only social anxiety or depressive disorders. We propose morning plasma and saliva cortisol levels as potential physiological indicators for supporting the evaluation of symptoms' severity and treatment progress in children with GAD and comorbid depressive disorder.